Lower extremity stiffness characteristics in running and jumping: Methodology and implications for athletic performance - Ryu, J. H. (Korean Journal of Sport Biomechanics, 2018)
Objective: The human body is often modelled as a spring-mass system. Lower extremity stiffness has been considered to be one of key factor in the performance enhancement of running, jumping, and hopping involved sports activities. There are several different classification of lower extremity stiffness consisting of vertical stiffness, leg stiffness, joint stiffness, as well as muscle and tendon stiffness. The primary purpose of this paper was to review the literature and describe different stiffness models and discuss applications of stiffness models while engaging in sports activities. In addition, this paper provided a current update of the lower extremity literature as it investigates the relationships between lower extremity stiffness and both functional performance and injury. Summary: Because various methods for measuring lower extremity stiffness are existing, measurements should always be accompanied by a detailed description including type of stiffness, testing method and calculation method. Moreover, investigator should be cautious when comparing lower extremity stiffness from different methods. Some evidence highlights that optimal degree of lower extremity stiffness is required for successful athletic performance. However, the actual magnitude of stiffness required to optimize performance is relatively unexplored. Direct relationship between lower extremity stiffness and lower extremity injuries has not clearly been established yet. Overall, high stiffness is potentially associate risk factors of lower extremity injuries although some of the evidence is controversial. Prospective injures studies are necessary to confirm this relationship. Moreover, further biomechanical and physiological investigation is needed to identify the optimal regulation of the lower limb stiffness behavior and its impact on athletic performance and lower limb injuries.